Biophysical criteria used by farmers for fallow selection in West and Central Africa - Norgrove, L.; Hauser, S. (Elsevier, 2016)
In many parts of the humid Tropics, slash and burn shifting cultivation, incorporating a fallow phase, is the most common farming method, encompassing a broad diversity of techniques. The ecological productivity and sustainability of such systems depend upon the crop:fallow time ratio. Farmers often have biophysical criteria by which to match parcels to cropping systems and decide, for example, when to recultivate a fallow. In this paper, we collate reports of indicators used by farmers to aid in fallow choice from across the agronomic, forestry, ecological, and anthropological literature. We found 27 examples of farmers using such biophysical indicators. Examples found were from eight countries across West and Central Africa. The literature review showed that farmers rank fallow age usually first, followed by vegetation composition, the presence of indicator plants, and earthworm casts. 53 indicator plant species were identified across the region of which 37 were said to indicate soil fertility, 13 soil infertility and 3 either fertility or infertility, depending on their growth characteristics. The most exhaustive lists of indicator plants were reported from southern Cameroon, the Ashante region of Ghana and south west Nigeria. Chromolaena odorata was the most frequently mentioned plant indicator species. The trees Triplochiton scleroxylon and Terminalia superba and the grass were each mentioned, generally as soil fertility indicators, in three areas. Other species mentioned multiple times were Aframomum sp., Andropogon gayanus, Ceiba pentandra, Milicia excelsa, Triumfetta cordifolia and Trema guineensis. Farmers in West and Central Africa have identified indicators for selecting which fallow plots to recultivate. Fallow age, vegetation composition, the presence of indicator plants, particularly C. odorata, and earthworm casts all have some logical scientific basis and farmers observations are supported by the results of scientific studies. There is a lack of documentation of farmers' knowledge and more studies should be conducted. Such knowledge should form the foundation of any suggested interventions in farming systems in the region and provide information to farmers in communities where such knowledge is not currently applied.